PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL SEBAGAI STRATEGI MENGHADAPI AEC - Siahaan, Sisca May Retta; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the influence of independent commissioner, the frequency of meeting of board of commissioner, the audit committee size, the frequency of meeting of audit committee, institutional ownership, government ownership and foreign ownership to the intellectual capital disclosure on the companies which are listed in Indonesia Stock Exchange. The samples have been selected by using purposive sampling technique and 21 banking companies which have published their annual report in 2010-2014 periods have been selected as samples, so there are 105 firm years that meet the criteria of the sample The statistical method uses multiple regressions analysis, goodness of fit test / F test with 0.00 significance value or models which have been used in this research have met the fit criteria, the determination coefficient test with Adjusted R Square value (Adjusted R2) is 0.477 or 47.7%, all independent variables can explain the dependent variable, and partial test (t-test). This research has been processed by using SPSS version 16. It has been found from the result of the research that the frequency of meeting of board of commissioner, the frequency of meeting of audit committee, institutional ownership, government ownership and foreign ownership have significant and positive influence to the intellectual capital disclosure whereas the proportion of independent commissioner and the audit committee size do not have any influence to the intellectual capital disclosure.Keywords: Good Corporate Governance, Ownership Structure, Intellectual Capital Disclosure